Violência urbana em Novo Hamburgo: notas introdutórias - Margarete Panerai Araújo; Daniela Müller de Quevedo; Luciana Hoppe; Suzel Lisiana Jansen; Cássia Rebelo Hofstatter (Ciências Sociais Unisinos)
This article discusses the importance that violence is acquiring at all levels of society. Nowadays, the subject "violence" is accepted as a result of a process that determines both culture and the economic, social and political values. The article investigates data about the state of Rio Grande do Sul and the municipality of Novo Hamburgo. The latter was the 4th most violent municipality in Rio Grande do Sul in 2004 as far as the homicide rate is concerned. The data lead to the conclusion that in such a context civil society is insecure and afraid of violence. They also show the importance of promoting public policies.